Wave-breaking limits for relativistic electrostatic waves in a one-dimensional warm plasma - Trines, R; Norreys, P (2006)
The propagation of electrostatic plasma waves having relativistic phase speed and amplitude has been studied. The plasma is described as a warm, relativistic, collisionless, nonequilibrium, one-dimensional electron fluid. Wave-breaking limits for the electrostatic field are calculated for nonrelativistic initial plasma temperatures and arbitrary phase velocities, and a correspondence between wave breaking and background particle trapping has been uncovered. Particular care is given to the ultrarelativistic regime (γ2 kB T0 (me c2) 1), since conflicting results for this regime have been published in the literature. It is shown here that the ultrarelativistic wave-breaking limit will reach arbitrarily large values for γ →∞ and fixed initial temperature. Previous results claiming that this limit is bounded even in the limit γ →∞ are shown to suffer from incorrect application of the relativistic fluid equations and higher, more realistic wave-breaking limits are appropriate. © 2006 American Institute of Physics.